Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
x²+1/x² = [tex] (x + 1/x)^{2} [/tex] - 2 * x * ( 1 / x) = ( 2 + √3 + 2 - √3)^2 - 2 = 16 - 2 = 14.
[tex]x^2+ \frac{1}{x^2} =x^2+2\cdot x\cdot \frac{1}{x} +(\frac{1}{x})^2-2\cdot x\cdot \frac{1}{x} =(x+\frac{1}{x})^2-2\\\\x=2+ \sqrt{3} \ \ \ \Rightarrow\ \ \ x+ \frac{1}{x} =2+ \sqrt{3}+ \frac{1}{2+ \sqrt{3}} =2+ \sqrt{3}+ \frac{2- \sqrt{3} }{(2+ \sqrt{3})(2- \sqrt{3})} =\\\\=2+ \sqrt{3} + \frac{2- \sqrt{3} }{4-3} =2+ \sqrt{3} +2- \sqrt{3} =4\\\\x+ \frac{1}{x} =4\ \ \ \Rightarrow\ \ \ (x+\frac{1}{x})^2-2=4^2-2=16-2=14[/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.